The Role of Pirani Scoring System in the Treatment of Congenital Clubfoot by the Ponseti Method - Zahoor Wahl Soomro, Karam All Shah, Naseer Ahmed Memon (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To assess the effectiveness of the Pirani score for the treatment of idiopathic congenital clubfoot deformity by the Ponseti Method. Method: This observational cross-sectional study was conducted at Department of Orthopedic Surgery Peoples University of Medical & Health Science Nawabshah (SBA) from January 2015 to December 2016. Total number of 100 patients with 158 clubfeet of idiopathic congenital talipes equinovarus deformity upto the age of 2 years of either sex were included. Patients were evaluated and graded for severity by using the Pirani scoring system, which is based on physical examination and require no radiographic measurements or other special investigations. Results were analysed statistically. Results: Male were 68% (68). There was correlation between the Pirani score and the number of casts to achieve correction and the need for tenotomy. Out of 100 patients 94 patients were obtained correction while 6 patients underwent posteromedial release ( PMR) surgery. The total number of casts with average of 5.7 and the range of 4-8 casts, and percutaneous tenotomy was performed in 84 patients. At the final stage of Ponseti technique the mean comparison of Pirani scoring system was significantly decreased from the initial stage. Conclusion: Pirani scoring system is a reliable, effective, and simple method to determine severity and monitor progress in the management ofclubfoot deformity by the Ponseti method.